USE OF MANAGEMENT INFORMATION SYSTEMS IN DILARA LAUNDRY - Hani, Fildzah; Nasution, Muhammad Irwan Padli; Sundari, Sri Suci Ayu (Bina Bangsa International Journal of Business and Management, 2024)
This paper aims to evaluate all aspects of the feasibility of the laundry business from Dilara Laundry. The increasing number of residents provides opportunities from various businesses, one of which is the laundry service business. Every housewife definitely needs these services because washing is a household need. Dilara Laundry is located in a strategic place that can be easily reached by consumers. Dilara laundry also provides very affordable prices and has various programs that can benefit consumers. In addition, Dilara Laundry provides shuttle facilities. Based on research from various aspects, it can be concluded that Dilara Laundry can be said to be feasible to run.